Free Radical, Oxidative Stress and Its Roles on Inflammatory Response - Putu Oky Ari Tania (Berkala Kedokteran, 2018)
Abstract: Chronic inflammation contributes to the occurrence of various metabolic diseases and even cancer. Chronic inflammation results from excessive response of free radicals. Free radicals are triggered by various agents and oxidation processes in the body as Reactive Oxygen Stress (ROS). The high level of free radicals (oxidants), without adequate intake of antioxidants will lead to oxidative stress conditions. Oxidative stress triggers persistent of inflammation. The formation of ROS is difficult to avoid because it can be generated from cellular metabolic processes. Therefore, we should intake adequate of antioxidants and avoid the various agents induces ROS in everyday life. Keywords : ROS, Stress Oxidative, Inflammation